2017
DOI: 10.1088/1757-899x/217/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Fuel Characterization of Newly Discovered Nigerian Coals

Abstract: This study seeks to characterize and highlight the fuel properties, rank, and classification of coals from Ihioma (IHM) and Ogboligbo (OGB) in Imo and Kogi states of Nigeria, respectively. The fuel properties were examined based on ultimate, proximate, and bomb calorific analyses. The results indicated that IHM coal contains comparatively higher C and H but lower O, N, and S content than OGB. In addition, the nitrogen (N) and sulphur (S) content for both coal samples were above 0.7 wt.% and 1.5 wt.%, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…In this study, the moisture content of below 10% observed for all the coal samples are within the acceptable limits for electric power generation or conversion into value-added products (Chukwu et al 2016;Akinyemi et al 2020a). In contrast, the volatile matter (VM) is an important factor for determining not only the coal rank but also its suitability for potential energy recovery from thermal processes such as combustion and pyrolysis (carbonisation) (Speight 2012;Nyakuma 2016). The findings also showed that AKZ contains the highest fixed carbon (FC) content, which is typically inversely proportional to the VM content.…”
Section: Kinetic Analysesmentioning
confidence: 77%
“…In this study, the moisture content of below 10% observed for all the coal samples are within the acceptable limits for electric power generation or conversion into value-added products (Chukwu et al 2016;Akinyemi et al 2020a). In contrast, the volatile matter (VM) is an important factor for determining not only the coal rank but also its suitability for potential energy recovery from thermal processes such as combustion and pyrolysis (carbonisation) (Speight 2012;Nyakuma 2016). The findings also showed that AKZ contains the highest fixed carbon (FC) content, which is typically inversely proportional to the VM content.…”
Section: Kinetic Analysesmentioning
confidence: 77%
“…Table 1. Proximate, Ultimate and Sulphanal analysis of BMK and IHM (Nyakuma et al 2017) 3. Results and Discussion…”
Section: Process Descriptionmentioning
confidence: 99%
“…The findings also showed that AKZ contains the highest fixed carbon (FC) content, which is typically inversely proportional to the VM content. The FC of coal is a measure of the estimated coke yield after devolatilization from carbonisation or slow pyrolysis (Nyakuma 2016).…”
Section: Physicochemical Propertiesmentioning
confidence: 99%